Barrier Analysis as a Tool to Inform Extension Activity Planning: Insights from Guatemala - Alene Seiler Martinez; Theresa Pesl Murphrey; Gary Wingenbach; Leonardo Lombardini (Journal of International Agricultural and Extension Education, 2018)
Over the past decade, renewed emphasis has been placed on extension services in developing countries to reduce rural poverty and improve food security. Despite this emphasis, complex physical, political, and socioeconomic environments in developing countries pose significant difficulties to extension agents’ success rates of adoption of new practices and/or behavior change among rural populations. In addition, agents have meager resources at their dis-posal.Development programs in the health sector have had success with employing behavior change theories for program design, driven by the Barrier Analysis as amethod for gather-ing data about target populations. Theory and research suggest this method provides key in-formation about why a target population might adopt new practices. If extension agents in developing countries such as Guatemala had access to such information, they might inten-tionally design interventions that lead to adoption.This paper provides an examination of ex-amples from the field in Guatemala that illuminate ways in which extension agents can gain formative data that when analyzed, may shape how they encourage adoption of new prac-tices. The implications of this paper suggest that using formative data gathering for planning interventions can lead to the behavior changeextension agents andtheir governments seek
Keywords: program planning; formative research; Barrier Analysis; behavior change; extension; international development; Guatemala